Pengaruh Kemudahan Penggunaan Dan Promosi Cashback Terhadap Minat Mahasiswa Dalam Menggunakan Dompet Digital Shopeepay (Studi Kasus Pada Mahasiswa Universitas Singaperbangsa Karawang) - Fauzi, Firman; Sulaeman, Eman (Jurnal Ilmiah Wahana Pendidikan, 2023)
The use of digital wallets is becoming a favorite nowadays. People feel that using digital wallets makes daily transactions easier. Apart from convenience, using a digital wallet can also provide other benefits such as cashback obtained after transactions. This research aims to determine the effect of ease of use and cashback promotions on interest in using digital wallets among students. The research method used is a quantitative method with a descriptive and verification approach with the analytical technique used is multiple linear regression analysis. The results of this study indicate that ease of use has a significant effect on interest in using and cashback promotions do not have a significant effect on interest in using. However, simultaneously ease of use and cashback promotions both influence interest in using.